2021
DOI: 10.3389/fendo.2021.721202
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Key Candidate Genes and Chemical Perturbagens in Diabetic Kidney Disease Using Integrated Bioinformatics Analysis

Abstract: Globally, nearly 40 percent of all diabetic patients develop serious diabetic kidney disease (DKD). The identification of the potential early-stage biomarkers and elucidation of their underlying molecular mechanisms in DKD are required. In this study, we performed integrated bioinformatics analysis on the expression profiles GSE111154, GSE30528 and GSE30529 associated with early diabetic nephropathy (EDN), glomerular DKD (GDKD) and tubular DKD (TDKD), respectively. A total of 1,241, 318 and 280 differentially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Cardiofibrosis has a significant influence on the prognosis of heart diseases, which can be regulated by POSTN [ 47 , 48 ]. POSTN was also found to be associated with renal diseases, including diabetic kidney disease [ 49 ], immunoglobulin A nephropathy [ 50 ], and polycystic kidney disease [ 51 ]. Hence, regardless of the absence of a regulatory relationship of POSTN and FN1 with CRS, FN1 and POSTN may exert important biological functions in the pathogenesis of CRS.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiofibrosis has a significant influence on the prognosis of heart diseases, which can be regulated by POSTN [ 47 , 48 ]. POSTN was also found to be associated with renal diseases, including diabetic kidney disease [ 49 ], immunoglobulin A nephropathy [ 50 ], and polycystic kidney disease [ 51 ]. Hence, regardless of the absence of a regulatory relationship of POSTN and FN1 with CRS, FN1 and POSTN may exert important biological functions in the pathogenesis of CRS.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that VCAN is up-regulated in DKD and is associated with immune cell injury in diabetic kidney tissue. 47,48 TIMP1 is a pro-fibrotic protein that belongs to the TIMP family that exists in the extracellular matrix and is involved in the inhibition of degradation in the extracellular matrix and the promotion of cell proliferation. 49 Animal experiments have shown that TIMP-1 promotes fibrotic progression in renal tubular cells by exerting toxic effects; 50 however, the potential association between TIMP1 and DKD has yet to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Integrative bioinformatics analysis with larger sample sizes and more minor potential biases is superior to finding new molecular signatures ( 9 ). Different bioinformatics analyses for DKD have been reported ( 10 18 ). The datasets involved in those studies are either from type 1 diabetic kidney disease (T1DKD) ( 10 13 ) or type 2 kidney disease (T2DKD) samples ( 14 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Gao et al. performed integrative bioinformatics analysis of 3 human datasets associated with early T2DKD (pathologic stages I-III), glomerular DKD, and tubular DKD, respectively, and identified 7 candidate genes (SPARC, POSTN, LUM, KNG1, FN1, VCAN, PTPRO) significantly associated with the progression of DKD ( 18 ).…”
Section: Introductionmentioning
confidence: 99%